The Role of Lampung Provincial Government in Coffee Product Ratification as a Leading Local Economic Driver - Reza Nawafella Alya Parangu; Achmad Kanzulfikar (JURNAL TAPIS, 2026)
Coffee is one of the main agricultural commodities in Lampung Province and plays an important role in local economic development. Although Lampung is one of Indonesia’s largest coffee-producing regions, its coffee has not yet achieved strong competitiveness in global markets, and farmers still receive limited economic benefits. This study examines the role of the Lampung Provincial Government in strengthening coffee as a leading regional commodity and identifies the challenges affecting its development. A qualitative case study approach was used, with data collected through interviews, observations, and document analysis. The results show that the provincial government acts as a regulator, facilitator, coordinator, and innovator in supporting the coffee sector. However, the implementation of these roles is not yet optimal. Challenges include limited implementation of certification and geographical indication programs, unequal stakeholder participation, weak farmer bargaining power, and limited involvement of farmers in value-added activities. The findings indicate that the competitiveness of Lampung coffee is influenced not only by production factors but also by governance and institutional conditions. This study contributes to the literature on local economic development and collaborative governance by showing that successful commodity development requires strong collaboration among government, farmers, cooperatives, and businesses. Practically, the study highlights the need to strengthen farmer institutions, expand value-added processing, and improve coffee branding to increase competitiveness and farmer welfare.